Climate and agriculture in West Africa : quantification of climate change impacts on crop yields and evaluation of seasonal forecasts utility - (:unkn) unknown (My University, 2012)
In this thesis, we first aim at determining past and future climate changes in West Africa. This leads us to a review of all the studies assessing the impact of future climate changes on agricultural yields in the area, in order to give robust results. The median value of all relative changes of yield is - 11%, hence the relevance for future studies to define a large range of climatic scenarios, and to focus on the differences among cultivars and between the Northern and Southern parts of West Africa. Based on these conclusions, we next intend to evaluate the impact of future climate change on West African yields using a network of thirty five meteorological stations providing daily historical data (1961/1990). To do so, it is necessary for us to define thirty five climatic scenarios based on rainfall and temperature anomalies and to compute yields for three contrasted millet and sorghum cultivars. Results reveal a negative evolution of average yield, mainly driven by temperature rise. Rainfall anomalies can only compensate (positive anomaly) or aggravate (negative) this negative yield change. We also find that potential impacts are more pessimistic for cultivars with a constant cycle length. Given these previous findings about high year-to-year variability of rainfall (thus entailing a variability of yields) and given the uncertain future climate, we are led to study next what interest the farmers would have in having climatic information such as seasonal forecasts. These forecasts can be used to minimize the impacts of rainfall variability and are robust to climate change. We compute the value of such forecasts for millet growers in Niger, using a simple economic model which represents farmers' strategies (cropping practices, risk aversion). Results reveal a positive impact of such forecasts on average income, even for dry years and with a forecast accuracy close to a real one. This imperfect forecast leads to a +6.9% increase in income on the whole
Keywords: African Research